Study on existing nutritional condition of peri-urban dairies at Chittagong, Bangladesh - Hasanuzzaman, M; Ahaduzzaman, M; Begum, MR (International Journal of Agricultural Research, Innovation and Technology, 2014)
The study was aimed to observe the nutritive value of concentrate used in different dairy farms at peri-urban areas of Chittagong, Bangladesh. Ten (10) different concentrate feeds were randomly selected from ten different farms which analyzed for moisture, dry matter (DM), crude protein (CP), crude fiber (CF), nitrogen free extracts (NFE), ether extracts (EE), total ash (TA) and acid insoluble ash (AIA) and requirements of concentrate for unit production of milk was calculated. It was found that the nutritive value of individual feed concentrate of each farm varied significantly. The observed proportion of using feed ingredients was also significantly different among the farms. Finally, it may be summarized that the concentrate mixture used by the different farmers of peri-urban areas of Chittagong was different in regards to chemical composition, ingredients and amount required for milk production. DOI: http://dx.doi.org/10.3329/ijarit.v3i2.17844 Int. J. Agril. Res. Innov. & Tech. 3 (2): 49-53, December, 2013